2021
DOI: 10.1186/s12957-021-02145-1
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-three long-term survivors after cytoreductive surgery in patients with peritoneal metastases from colorectal cancer: a retrospective descriptive study

Abstract: Background Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) improves survival in selected patients with peritoneal metastasis (PM) from colorectal cancer (CRC). However, little has been reported on characteristics and clinical course of long-term survivors with CRC-PM beyond 5 years. The objective of this study was to identify the clinical and oncological features affecting long-term survival of CRC-PM after comprehensive treatment. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Of note, more than half (63.1%, 130/206) of the patients showed an SB-PCI = 0. In our previous study [32], the median SB-PCI for the entire cohort was 2 (IQR, 0-3). Between this present study and the previous one, the SB-PCI cannot be statistically compared, but these findings suggest that lower SB-PCIs than that of other abdominopelvic regions are needed for long-term survival.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Of note, more than half (63.1%, 130/206) of the patients showed an SB-PCI = 0. In our previous study [32], the median SB-PCI for the entire cohort was 2 (IQR, 0-3). Between this present study and the previous one, the SB-PCI cannot be statistically compared, but these findings suggest that lower SB-PCIs than that of other abdominopelvic regions are needed for long-term survival.…”
Section: Discussionmentioning
confidence: 85%
“…Also, about 90% of the long-term survivors and cured patients (180/206, 87.4%, and 77/84, 91.7%) achieved CC-0. The previous study [32] demonstrated that there was a statistically significant difference in CC-0 rates between long-term survivors and non-survivors (33/33 (100%) versus 141/203 (69.8%), p < 0.001). As such, these data indicate that low PCI and CC-0 are associated with long-term survival and cure in patients with peritoneal metastases from CRC, although a statistical comparison should not be conducted because of the different datasets.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…First is the disease type, and the other is the extent and volume of peritoneal spread. Based on current literature pseudomyxoma peritonei, mesothelioma, peritoneal metastases of tumors of appendicular and colorectal origin, and ovarian cancers have shown benefit with CRS and HIPEC [15][16][17][18][19][20][21][22]. CT scan of the abdomen and pelvis is used to assess volume and extent of peritoneal spread and helps to determine feasibility of optimal cytoreduction.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent trials reported no benefits in terms of survival [ 20 , 22 , 23 ]. In addition, a study suggested that one patient over seven who undergo CRS achieves long-term survival [ 24 ]. In addition, due to the extent of the disease and the surgeon’s experience and skills, not all patients can undergo complete/satisfactory CRS.…”
Section: Introductionmentioning
confidence: 99%